Defining the concept of family caregiver burden in patients with schizophrenia: a systematic review protocol - Zahra Tamizi; Masoud Fallahi-Khoshknab; Asghar Dalvandi; Farahnaz Mohammadi-Shahboulaghi; Eesa Mohammadi; Enayatollah Bakhshi (Systematic Reviews, 2019)
Abstract Background Since the deinstitutionalization policy, in psychiatric hospitals, the care of patients with schizophrenia was left to their families which has been imposing a heavy burden on them. Family caregiver burden could have consequences for caregivers, patients, and the society. There is very little consensus on the definition and dimensions of the caregiver burden, which leads to a lack of consistency in the results of research. Thus, the present study was aimed to redefine the family caregiver burden of patients with schizophrenia. Methods The databases PubMed, Scopus, Web of Science, MEDLINE (Via Ovid), ProQuest, SCI, Magiran, SID, and IranDoc will be searched from 1940 to 2018 using subject headings and appropriate terms in both Farsi and English languages. Also, gray literature and the reference list of included articles will be used to offer an appropriate definition of the family caregiver burden in patients with schizophrenia. Two independent reviewers will participate in study selection, data collection, and quality assessment steps. The result will be presented in tabular form, and meta-synthesis will be performed. Discussion The result of this systematic review will help present the comprehensive definition of the family caregiver burden in patients with schizophrenia according to its evolutionary trend. Systematic review registration PROSPERO CRD42018099372